A Study of Characteristics of Musculoskeletal Injury in Female Elite Junior Golfers - Kwang-Jun Kim; Dong Hyun Yoon (Asian Society of Kinesiology, 2024)
OBJECTIVES The purpose of this study is to compare and analyze the group differences in musculoskeletal injury and rehabilitation and physical exercise according to the level of handicap for female elite amateur golfers. METHODS We sampled 191 female golfers (mean age 17.61, SD=1.50) and examined individual and golf-specific characteristics, and medical history. Subgroups with different handicaps (<0, 0-3, 4-6, 7-9, >10) were compared using one-way analysis of variance and frequency analysis tests. RESULTS In the sub-group divided by handicap level, there were significant differences between the groups in terms of career, scoring average, and greens in regulation, and in the injury-related questions, they responded in the order of muscle pain, blisters, and ligament rupture. The response rate for the body parts of injury was high in the order of wrist, lower back, and shoulder, and statistically significant differences between the groups in terms of fracture and shoulder, hand, and lower back. In the questionnaire on warm-up, stretching and practice swing showed significant differences between groups, and cool-down exercise showed significant differences only in practice swing. Finally, Fitness training time showed a significant difference between groups. CONCLUSIONS In conclusion, the purpose of this study is to provide data for understanding golf injury and prevention of injury, and the results of this study can help inform further research on preventing injuries in golfers' most frequent injury areas and further establishing injury prevention management strategies.